2020
DOI: 10.12928/dpphj.v14i2.2235
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Work Fatigue Symptoms on Bus Service Officers of PT TransJakarta Corridor VI Ragunan

Abstract: Background: Work fatigue is a source of problems for workers’ health and safety. According to the Ministry of Manpower, data on occupational accidents in 2017 indicate that the number of occupational injuries was 80,392 cases. This study aims to find out factors related to fatigue symptoms on Bus Service Officers of PT TransJakarta, including age, sex, nutritional status, marital status, medical history, workload, work stress, work shift, and ergonomic status. Method: This study uses an analytical descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Work positions that do not comply with the predetermined standards, repetitive activities, unnatural work postures, and body positions far from the center of gravity will cause muscle fatigue (Tarwaka, 2014). If ergonomic status is considered as work position, then this research is in line with Lukman's (2020) research stating that ergonomic status had a significant correlation with work fatigue. The results of the study is also in line with research by (Putriwijaya, Berniyanti and Diyatri, 2016) which found that there was a significant relationship between work position and lactic acid levels with musculoskeletal problems.…”
Section: Correlation Between Work Position and Physical Fatiguesupporting
confidence: 82%
“…Work positions that do not comply with the predetermined standards, repetitive activities, unnatural work postures, and body positions far from the center of gravity will cause muscle fatigue (Tarwaka, 2014). If ergonomic status is considered as work position, then this research is in line with Lukman's (2020) research stating that ergonomic status had a significant correlation with work fatigue. The results of the study is also in line with research by (Putriwijaya, Berniyanti and Diyatri, 2016) which found that there was a significant relationship between work position and lactic acid levels with musculoskeletal problems.…”
Section: Correlation Between Work Position and Physical Fatiguesupporting
confidence: 82%